Pengembangan Kapasitas Pegawai Bagian Humas Sekretariat DPRD Kota Tidore Kepulauan Dalam Pelayanan Informasi Publik - Taduho, Sahril (JURNAL ILMIAH SOCIETY, 2016)
As a matter of fact, public relation perseptions and stigmatization commonly become obstacles for the Public Relation Division of City Secretariat of Tidore Island. The aim of this research is to know the form ofÂ building capacity reinforcement through education and training in public information service at House of Representative of Tidore Island City. The method applied in this research is descriptive qualitative. Observation, interview, and documentation research were the techniques in collecting the data as the research subject divided into key informants and prime informants in total of eight people. The descriptive data anlysis technique described phenomenons based on the field following the steps as follow: data reduction phase, data presentation, and data verification or conclusion. Based on the filed reserach showed that in capacity building of House of Representative public relation division officilas of Tidore Island City are highly depended on education and training to raise the service in the organization public information, therefore the substantive item seen by the society was the less maximal effort shown caused by the unprofesional human resources. The efforts toward the building capacity had not been done by the officials to answer the demand and need in community service of public relation division officials at House of Representative of Tidore Island City. Based on the findings, it can be concluded that the building capacity by education and training of public relation officials at House of Representative Secretariat of Tidore Island City is an urgent thing to reach the aim of the organization. Fungtional training such as public relation technique, jurnalism technique, seminars, discussion that relate to the responsibilities are needed tobe possesed. Keyword : Capacity Building, Human Relationship